Existence, uniqueness, and stability of fractional hepatitis B epidemic model - Khan, Amir; Hussain, Ghulam; İnç, Mustafa; Zaman, Gul (Aip Publishing, 2020)
This paper describes the existence and stability of the hepatitis B epidemic model with a fractional-order derivative in Atangana-Baleanu sense. Some new results are handled by using the Sumudu transform. The existence and uniqueness of the equilibrium solution are presented using the Banach fixed-point theorem. Moreover, sensitivity analysis complemented by simulations is performed to determine how changes in parameters affect the dynamical behavior of the system. The numerical simulations are carried out using a predictor-corrector scheme to demonstrate the obtained results.
Keywords: Mathematical-Analysis; Transmission; Vaccination; Systems; Virus